Identifikasi Postur Kerja dengan Metode Owas untuk Memperbaiki Postur Kerja Guna Mengurangi Musculoskeletal Disorder - Spalanzani, Widya (Jurnal Jaring SainTek, 2023)
Production activities at manufacture companies are often inconvenient. One of them is due to the incompatibility of workers anthropometry with the work facilities used. Disergonomics like this will cause complaints in the skeletal system. Complaints to this damage are termed musculoskeletal disorder (MSDS). The production process of making shoes at UD. Kurnia at the subordinate work station identified that work posture has the potential to cause injury to the arm, back and leg muscles with a percentage of 66.67%, 68.89% and 30%. So it is necessary to improve work posture. In this study, the OWAS method was used to identify and evaluate hazardous work postures. Meanwhile, to improve work posture, work facilities are designed using anthropometric data for subordinate work station workers. Owas identification results show that the work posture is more ergonomic. Then the results of the WinOwas software show that the improvement of work posture with the design of work facilities is included in category 1. Which means that the work posture is not dangerous. So it is directly believed that workers complaints on skeletal muscles or MSDs at subordinate work stations can be minimized.